2008
DOI: 10.1080/00150190802438033
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Scattering, Short Range Order and Nanodomains in the Paraelectric SbSI

Abstract: The ferroelectric crystal structure of SbSI is built of [Sb(S,I)] ∞ chains parallel to [001] axis. In the paraelectric phase the crystal structure is disordered. Each atom is shifted from the xy mirror plane by z up or down along [001]. The Reverse Monte Carlo (RMC) simulation of diffuse scattering revealed a complicated picture of the short and medium range order. The chains are not uniform but consist of sections of different length and opposite polarity. The distribution of these sections revealed by RMC sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, the same authors veried this information by a detailed study of diuse scattering in the crystal structure of SbSI at 320 K [8]. In [8] the average crystal structure of SbSI is described by the space group Pnam in which the [Sb(S,I)] ∞ chains are not uniform but consist of sections of dierent length and opposite polarity. These sections form nanodomains elongated in the [001] direction [8].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, the same authors veried this information by a detailed study of diuse scattering in the crystal structure of SbSI at 320 K [8]. In [8] the average crystal structure of SbSI is described by the space group Pnam in which the [Sb(S,I)] ∞ chains are not uniform but consist of sections of dierent length and opposite polarity. These sections form nanodomains elongated in the [001] direction [8].…”
Section: Introductionmentioning
confidence: 76%
“…For example, this structure was reported for the SbSI crystals at temperatures 308 K [6] and 333 K [7]. However, the same authors veried this information by a detailed study of diuse scattering in the crystal structure of SbSI at 320 K [8]. In [8] the average crystal structure of SbSI is described by the space group Pnam in which the [Sb(S,I)] ∞ chains are not uniform but consist of sections of dierent length and opposite polarity.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…We came to the conclusion that the fractional atomic displacements of all atoms up and down from the xy mirror plane in SbSBr and SbSI crystals [11] in average structure of paraelectric phase are created by strong anharmonicity of low-frequency B 1u vibration modes along the c(z)-axis. This strong anharmonicity is created by interaction between phonons.…”
Section: Phase Transitions 71mentioning
confidence: 99%
“…Lukaszewicz et al [11] investigated the SbSI crystal structure in a broad temperature range. They found that in paraelectric phase the crystal structure of SbSI at 320 K is disordered.…”
Section: Introductionmentioning
confidence: 99%